MINING MANAGEMENT LICENSING: OPPORTUNITIES AND CHALLENGES FOR INDIGENOUS COMMUNITIES - Freddi Agus Hutapea; Henry Aspan; Abdul Rahman Maulana Siregar (CV. RADJA PUBLIKA, 2024)
According to Presidential Regulation of the Republic of Indonesia Number 70 of 2023 concerning Allocation of Land for Investment, mining business permits may be granted to community organizations, as explained in Article 2 paragraph 1 letter f, Article 4 paragraph (5) letter c, Article 9, and Article 12 paragraph (1). This regulation also opens up the possibility of land allocation for various types of business entities, from small to large scale. However, one thing that is not yet clear is how indigenous communities can be more involved in mining management. That when talking about mining management permits for communities, the importance of accommodating indigenous communities is not only limited to the organizational level. Management of mineral and coal resources should contribute significantly to the economy and welfare of indigenous communities. Clear regulations are needed regarding the recognition and protection of the rights of indigenous communities as well as increasing the capacity of indigenous communities in the mining sector. This can be implemented through collaboration with BUMN in the mining sector as the aim is not only to focus on profit but also on community welfare as an agent of development.